2012
DOI: 10.1111/j.1477-2574.2012.00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Portal biliopathy in patients with non-cirrhotic portal hypertension: does the type of surgery affect outcome?

Abstract: Portal biliopathy was reversed in 38 of 43 patients by either portosystemic shunting or splenectomy-devascularization. In five patients, direct biliary decompressive procedures were required because of shunt blockage or a non-reversible biliary stricture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 18 publications
(42 reference statements)
0
40
0
1
Order By: Relevance
“…Benefits from PSS include regression of changes seen in early cholangiopathy, 35,36 complete regression of biliary obstruction in about 60-88% of patients 11,19,20,35,37 with further interventions needed for persistent biliary obstruction in only 25-30%. 20 The remaining patients usually remain asymptomatic, even though regression of cholangiographic changes is incomplete, suggesting arrest or slowing-down of progression after PSS.…”
Section: How To Treat?mentioning
confidence: 99%
“…Benefits from PSS include regression of changes seen in early cholangiopathy, 35,36 complete regression of biliary obstruction in about 60-88% of patients 11,19,20,35,37 with further interventions needed for persistent biliary obstruction in only 25-30%. 20 The remaining patients usually remain asymptomatic, even though regression of cholangiographic changes is incomplete, suggesting arrest or slowing-down of progression after PSS.…”
Section: How To Treat?mentioning
confidence: 99%
“…One of the strong arguments in favor of operative management has been the fact that surgery is a onetime procedure, does not require repeated hospital visits, which is particularly relevant for the majority of EHPVO patients who come from areas where specialized medical help and access to endotherapy may not be available. 11 In many surgical series, there are a group of about 20-47% of patients who are deemed as nonshuntable due to a lack of any suitable veins. This is because the entire portal venous system is obliterated and replaced by extensive collaterals.…”
Section: Management Of Portal Cavernoma Cholangiopathy-overviewmentioning
confidence: 99%
“…Chattopadhyay et al reported that patients who underwent these nonshunt procedures also had a significant reduction in their serum bilirubin levels. 11 Splenic artery ligation leads to reduction in the portal blood flow and portal pressure, which may lower the pressure in the pericholedochal collaterals leading to symptomatic improvement in PCC.…”
Section: Management Of Portal Cavernoma Cholangiopathy-overviewmentioning
confidence: 99%
See 2 more Smart Citations